Astragalin from Thesium chinense: A Novel Anti-Aging and Antioxidant Agent Targeting IGFR/CD38/Sirtuins - Ruifeng Wang; Anping Ding; Jiaye Wang; Jiaxue Wang; Yujie Zhou; Miao Chen; Shuang Ju; Mingpu Tan; Zengxu Xiang (MDPI AG, 2024)
Astragalin (AG), a typical flavonoid found in Thesium chinense Turcz (T. chinense), is abundant in various edible plants and possesses high nutritional value, as well as antioxidant and antibacterial effects. In this study, we initially predicted the mechanism of action of AG with two anti-aging and antioxidant-related protein targets (CD38 and IGFR) by molecular docking and molecular dynamics simulation techniques. Subsequently, we examined the anti-aging effects of AG in Caenorhabditis elegans (C. elegans), the antioxidant effects in zebrafish, and verified the related molecular mechanisms. In C. elegans, AG synergistically extended the lifespan of C. elegans by up-regulating the expression of daf-16 through inhibiting the expression of daf-2/IGFR and also activating the AMPK and MAPK pathways to up-regulate the expression of sir-2.1, sir-2.4, and skn-1. In oxidatively damaged zebrafish embryos, AG demonstrated a synergistic effect in augmenting the resistance of zebrafish embryos to oxidative stress by up-regulating the expression levels of SIRT1 and SIRT6 within the zebrafish embryos system via the suppression of CD38 enzymatic activity and then inhibiting the expression of IGFR through high levels of SIRT6. These findings highlight the antioxidant and anti-aging properties of AG and indicate its potential application as a supplementary ingredient in aquaculture for enhancing fish health and growth.